Analisis Pendapatan Usaha Keramba Air Tawar Di Pesisir Sungai Poso: Studi Kasus Di Kelurahan Sangele Kecamatan Pamona Puselemba Kabupaten Poso - Nolanda Tamodenje; Mikhael Jibrael Balo; Feliks Arfid Guampe (Fakultas Ekonomi Universitas Kristen Tentena, 2023)
This study aims to determine the business income of freshwater cages on the Poso River Coast, a case study in Sangele Village, Pamona Puselemba District, Poso Regency using qualitative methods. Interview, observation and documentation techniques are techniques for obtaining data. Key informants were determined as many as two cage fish entrepreneurs who were considered to be able to meet the data to achieve research objectives. Data analysis uses qualitative descriptive techniques by arranging research findings into categories, synthesizing, arranging into patterns, and making conclusions so that they are easy to understand. The results showed that MT cage business revenue amounted to Rp.9,999,960 and JJ amounted to Rp.30,000,000. The amount of fixed costs incurred by MT amounted to Rp.285,632, JJ amounted to Rp.413,968. MT variable costs amounted to Rp.3,870,000, JJ amounted to Rp.13,125,000 and MT Total Costs amounted to Rp.4,155,632, JJ amounted to Rp.13,538,968. From the total revenues and costs, the net income of cage businesses per production season respectively MT amounted to Rp. 5,844,328 and JJ amounted to Rp. 16.461.032.